Stability and structure of lean swirling spray flames with various degrees of prevaporization. Issue 2 (June 2023) - Wang, Jiayi; de Oliveira, Pedro M.; Pathania, Rohit Singh; El Helou, Ingrid; Mastorakos, Epaminondas
Achieving full premixing and complete evaporation in lean prevaporized premixed combustors is challenging as it depends on the spray injector characteristics, prevaporisation strategy, and flow conditions. This article experimentally explores the stability and structure of a turbulent swirling n -heptane spray flame under various degrees of prevaporization. The results show that preheating the air to 343 K and 393 K has little effect on the lean blow-off velocity, while recessing the fuel injection significantly decreases the lean stability limit. To correlate these limits, various attempts to define a Damköhler number were made, but unlike previous studies with no prevaporisation, the difficulty in defining laminar flame speed in the present case does not allow a single correlation to work for all degrees of prevaporization. Four stable cases that differ in equivalence ratio, air preheat temperature, and fuel injection recess are investigated using one-dimensional PDA, OH* chemiluminescence and CH 2 O-planar laser-induced fluorescence (PLIF). Cases without fuel injection recess or air preheat exhibit a conical-shaped heat release zone near the shear layers. Preheating the air to 393 K reduced the Sauter mean diameter, increased prevaporization, and enabled a second heat release zone downstream of the fuel injection. Recessing the fuel injection by 25 mm reduced droplet velocities and led to a semi-spherical instead of a conical heat release zone. The CH 2 O-PLIF signal without injection recess was high along the central axis and its distribution resembled that observed for spray jet flames. In contrast, with recessed spray injection, CH 2 O was mainly found outside the central recirculation zone and only appeared inside during lean blow-off; similar to previous work with premixed flames. These findings show that different methods of prevaporization, which only differ by subtle changes in droplet characteristics, strongly impact flame stability. The present data can be used for turbulent flame modelling focusing on sprays and finite-rate kinetics.